2019
DOI: 10.1186/s42269-019-0172-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pawpaw leaf and seed meal composite mix dietary supplementation on haematological indices, carcass traits and histological studies of broiler chicken

Abstract: Background: The use of phytogenic feed supplement is now being considered in broiler production for enhancing their performance and health status. In this 42-day feeding trial, the effects of a diet supplemented with pawpaw leaf and seed meal composite mix (PCM) on hematological indices, carcass, internal organs weights, and histology of the liver and testis of broiler chickens was assessed. Methods: Total number of 396 1-day-old Arbor Acres broiler chicks were distributed to six dietary treatments: (diet 1; 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
4
8
0
Order By: Relevance
“…Furthermore, dietary inclusion of POLM did not influence the relative organs weights in experimental broiler chickens. The outcomes of our present study are in agreement with Oloruntola [53], who observed that the relative internal organs weights of the broilers were not influenced by dietary inclusion of seed meal and pawpaw leaf meal. Similar observations were described in the work by Rubio et al [77] and Vispute et al [13], where dietary addition of phytobiotics did not influence the relative organs weights in broiler chickens.…”
Section: Relative Internal Organs Weightssupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, dietary inclusion of POLM did not influence the relative organs weights in experimental broiler chickens. The outcomes of our present study are in agreement with Oloruntola [53], who observed that the relative internal organs weights of the broilers were not influenced by dietary inclusion of seed meal and pawpaw leaf meal. Similar observations were described in the work by Rubio et al [77] and Vispute et al [13], where dietary addition of phytobiotics did not influence the relative organs weights in broiler chickens.…”
Section: Relative Internal Organs Weightssupporting
confidence: 93%
“…In another experiment, Gilani et al [ 11 ] examined the efficacy of organic acids and phytobiotics (possessing flavonoids) in poultry feed as alternatives to AGPs, observing significant increases in RBC and WBC counts, as well as an increase in PCV in broiler chickens. Similarly, broiler chickens fed Garden cress ( Lepidium satvium ) seed powder [ 51 ], cayenne pepper ( Capsicum frutescens ) and turmeric ( Curcuma longa ) powders [ 52 ], and pawpaw leaf and seed meal [ 53 ] showed increased values of Hb, PCV, and RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…In another experiment, Gilani et al (2018) examined the efficacy of organic acids and phytobiotics (possessing flavonoids) in poultry feed as alternatives to AGPs, observing significant increases in RBC and WBC counts, as well as an increase in PCV in broiler chickens. Similar observations were observed when broiler chickens were fed Garden cress (Lepidium satvium) seed powder (Shawle et al, 2016), cayenne pepper (Capsicum frutescens) and turmeric (Curcuma longa) powders (Adegoke et al, 2018), and pawpaw leaf and seed meal (Oloruntola, 2019). Isaac et al (2013) stated that haematological components, which consists of red blood cells, white blood cells or leucocytes, Mean Corpuscular Haemoglobin and Mean Corpuscular Haemoglobin Concentration are valuable in monitoring feed toxicity, especially, with feed constituents that affect the blood as well as the health status of farm animals.…”
Section: Discussionsupporting
confidence: 69%
“…Also, dietary incorporation of fermented pineapple peel resulted in absent influence on the carcass characteristics of broiler strains (Heryandi et al, 2018). In respect to papaya leaf and seed, feeding papaya leaf (Oloruntola et al, 2018), seed (Bolu et al, 2009) or the blend of papaya leaf and seed (Oloruntola, 2019) did not influence the carcass characteristics of broiler chickens.…”
Section: Discussionmentioning
confidence: 86%